2021
DOI: 10.3390/ijerph18094526
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Silicone and Sarcoid Granulomas in a Patient with “Highly Cohesive” Silicone Breast Implants: A Histopathologic and Laser Raman Microprobe Analysis

Abstract: Foreign body giant cell (FBGC) reaction to silicone material in the lymph nodes of patients with silicone breast implants has been documented in the literature, with a number of case reports dating back to 1978. Many of these case reports describe histologic features of silicone lymphadenopathy in regional lymph nodes from patients with multiple sets of different types of implants, including single lumen smooth surface gel, single lumen textured surface gel, single lumen with polyethylene terephthalate patch, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
(57 reference statements)
0
12
0
1
Order By: Relevance
“…Prior research suggested the potential for silicone leakage directly from the PDMS elastomer shell using spectroscopic analysis. 8 , 9 Silicone leakage may occur due to shell degradation cause by mechanical forces and interactions with the body. Although the basic design of saline implants has been maintained, specific information about changes in manufacturing processes is not readily available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research suggested the potential for silicone leakage directly from the PDMS elastomer shell using spectroscopic analysis. 8 , 9 Silicone leakage may occur due to shell degradation cause by mechanical forces and interactions with the body. Although the basic design of saline implants has been maintained, specific information about changes in manufacturing processes is not readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the presumed inertness of silicone, leaked particles from implants can spread within the body, triggering inflammatory responses such as granuloma formation, and lymphadenopathy mimicking malignancies on positron emission tomography imaging. 6 , 9 , 10 These clinical observations underscore the need to investigate the systemic health complaints reported by patients with various types of breast implants.…”
Section: Discussionmentioning
confidence: 99%
“…Data on silicone leakage from cohesive gel SBIs is scarce, 21 , 22 and little data exist concerning leakage and migration. A recent case of silicone and sarcoid granulomas in a patient with highly cohesive SBIs was described in a 2021 study by Nanayakkara et al 23 …”
Section: Introductionmentioning
confidence: 99%
“…20 Data on silicone leakage from cohesive gel SBIs is scarce, 21,22 and little data exist concerning leakage and migration. A recent case of silicone and sarcoid granulomas in a patient with highly cohesive SBIs was described in a 2021 study by Nanayakkara et al 23 Large case series in which data on gel bleed and migration in patients with noncohesive and cohesive gel SBIs are compared are lacking. The aim of this study is to gain more clarity and insights about the prevalence of silicone leakage in patients with noncohesive or cohesive SBIs.…”
Section: Introductionmentioning
confidence: 99%
“…Timely detection of silicone leakage, due to ruptures or extensive bleeding from intact implants, is crucial to mitigate the risks of unpredictable silicone migration, as exemplified by disturbing case reports. Migrating silicone particles can induce inflammation leading to silicone-induced lymphadenopathy ( 7 ), acute respiratory distress syndrome ( 8 , 9 ), chronic pulmonary embolism ( 9 , 10 ), sarcoidosis ( 11 ) and scleroderma of the skin ( 12 ). Granuloma formation may occur ( 13 ), potentially resulting in embolism formation and hematological spread to, for example, the carotid artery leading to ocular muscle palsy ( 14 ).…”
Section: Introductionmentioning
confidence: 99%